A correlation study of ischiocavernosus muscle injury with different types of pelvic fractures and erectile dysfunction after pelvic fracture. Issue 4 (16th December 2020) - Chen, Zongping; Song, Tao; Zhuang, Yongxiang; Yan, Yong; Liu, Tong; Mao, Kaiyi; Li, Xu; Zou, Chenghong; Wen, Xin; Yao, Yuhong; Chen, Chao; Zhao, Sicong
Abstract: Objective: To explore the correlation between ischiocavernosus muscle injury (ICMI) with different types of pelvic fractures and erectile dysfunction (ED) after pelvic fracture. Design: Retrospective analysis of a prospective database. Setting: The study was carried out at the affiliated hospital of Zunyi Medical University. Patients/participants: A total of 776 male patients with pelvic fracture, aged 18 to 67 years, were recruited for this study by retrospective analysis, and based on the diagnosis of ED and the presence of ICMI, the participants were divided into ED and non-ED groups as well as ICMI and non-ICMI groups. Intervention: No. Main outcome measurements: ICMI, the type of pelvic fracture, International Index of Erectile Function-5 scores. Computed tomography/magnetic resonance imaging scans, electromyography (motor unit potential) was used to diagnose ICMI. Results: The International Index of Erectile Function-5 score was 19.7 ± 5.9. The incidence of ED was 27.3%, the duration time of ED was 30 ± 23 months, and the incidence of reversible ED was 39.6% and of irreversible ED was 60.4%. The incidence of ICMI was 29.4%, among which the incidence of unilateral injury was 57.9%, and the incidence of bilateral injury was 42.1%. Among all pelvic fractures, the incidence of pubic ramus fracture was 88.1%. Bilateral pubic ramus fractures, bilateral fractures of the ischial ramus, and ICMI were independent risk factors for ED after pelvic fracture. Bilateral pubic ramus fractures and pubic symphysis separation were independent risk factors for ICMI. Unilateral ICMI was an independent risk factor for reversible ED, while bilateral ICMI was an independent risk factor for irreversible ED. Conclusions: ICMI is associated with ED and may be a cause for ED, while pubic ramus fracture, ischial ramus fracture, and pubic symphysis separation may be the main causes of ICMI. Unilateral ICMI may be the main risk factor for transient ED, and bilateral ICMI may be the main risk factor for permanent ED.